Acoustic and vibration analysis of a turbocharger centrifugal compressor failure. (September 2022) - Sandoval, Oscar R.; Machado, Luiz Henrique Jorge; Hanriot, Vítor Mourão; Troysi, Fernanda; Faria, Marco Tulio C.
Highlights: Blade deburring of compressor wheel are chosen to study the turbocharger failures. Vibration amplitude with faulted blades is related with subsynchronous frequencies. Acoustic level increases in the frequencies 1.5 to 1.6 kHz in the faulted blades air outlet. Vibratory and noise response permit the characterization of operating failure. Abstract: The technology of internal combustion engines has improved to meeting international regulations, applying turbocharging as an effective method. However, the works under extreme conditions requires strict maintenance plans, since when it fails, it completely deteriorates the functioning of the turbocharged engine. In this work, two procedures are used to characterize some operating failures. Faulted blades are introduced in the compressor to simulate typical failures observed in automotive turbochargers. Four centrifugal compressors mounted with perfect and defected blades are used to compare changes during three failures steps, using experimental vibration and acoustic analyses. The vibratory response of the compressor is obtained by analyzing the vibration signals measured on the turbochargers. Furthermore, sound pressure measurements are performed to evaluate the noise radiation based on an acoustic wave decomposition technique. The experimental results rendered for the vibratory response and noise generation from the turbocharger compressor permit the characterization of automotive turbocompressor operating failures.